2021
DOI: 10.1371/journal.pmed.1003415
|View full text |Cite
|
Sign up to set email alerts
|

Early versus deferred anti-SARS-CoV-2 convalescent plasma in patients admitted for COVID-19: A randomized phase II clinical trial

Abstract: Background Convalescent plasma (CP), despite limited evidence on its efficacy, is being widely used as a compassionate therapy for hospitalized patients with COVID-19. We aimed to evaluate the efficacy and safety of early CP therapy in COVID-19 progression. Methods and findings The study was an open-label, single-center randomized clinical trial performed in an academic medical center in Santiago, Chile, from May 10, 2020, to July 18, 2020, with final follow-up until August 17, 2020. The trial included patie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
89
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(95 citation statements)
references
References 38 publications
3
89
0
1
Order By: Relevance
“…In the study by Altuntas et al, a higher rate of mechanical ventilation support was observed in patients receiving CP 20 days after diagnosis compared to three interval groups (< 5, 6-10, and 11-15 days, p = 0.001) [23]. We failed to find a significant effect of the time to CP infusion, regarding all primary and secondary outcomes, in accordance with a recently published randomized trial where no significant difference was observed in mortality or disease deterioration in early (< 7 days of symptom onset) vs. late CP administration [43].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In the study by Altuntas et al, a higher rate of mechanical ventilation support was observed in patients receiving CP 20 days after diagnosis compared to three interval groups (< 5, 6-10, and 11-15 days, p = 0.001) [23]. We failed to find a significant effect of the time to CP infusion, regarding all primary and secondary outcomes, in accordance with a recently published randomized trial where no significant difference was observed in mortality or disease deterioration in early (< 7 days of symptom onset) vs. late CP administration [43].…”
Section: Discussionsupporting
confidence: 85%
“…In most clinical trials, one to two units from one or different donors have been proposed for treatment. In some studies, only CP with arbitrarily defined high titers were used, resulting in significant reduction in the risk of death or disease progression [28,29,43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the screening phase of these manuscripts, 15 were excluded: three studies did not report mortality data or compared mortality rate with national registries (Bradfute et al, 2020;Dulipsingh et al, 2020;Perotti et al, 2020); for two studies, we were unable to assess our inclusion criteria (Anakli et al, 2021;Skrip et al, 2020); seven had no comparative group (Dulipsingh et al, 2020;Gonzá lez et al, 2020;Jaiswal et al, 2021;Madariaga et al, 2020;Olivares-Gazca et al, 2020;Tremblay et al, 2020;Valentini et al, 2020); and three studies made use of plasma from non-convalescent, generic donors (De-Simone et al, 2021;Faqihi et al, 2020;Kamran et al, 2021). Of the 25 studies included for the quantitative meta-analysis, 10 were RCTs (Agarwal et al, 2020;AlQahtani et al, 2020;Avendano-Sola et al, 2020;Balcells et al, 2021;Gharbharan et al, 2020;Horby et al, 2021;Li et al, 2020a;Libster et al, 2021;Rasheed et al, 2020;Simonovich et al, 2020), while the other 15 were non-randomized studies with different designs (Abolghasemi et al, 2020;Alsharidah et al, 2021;Altuntas et al, 2021;Budhiraja et al, 2021;Donato et al, 2021;Duan et al, 2020;Hegerova et al, 2020;Joyner et al, 2021;Liu et al, 2020;Omrani et al, 2021;Salazar et al, 2020a;Shenoy et al...…”
Section: Resultsmentioning
confidence: 99%
“…Of the 25 studies included for the quantitative meta-analysis, 10 were RCTs (Agarwal et al, 2020;AlQahtani et al, 2020;Avendano-Sola et al, 2020;Balcells et al, 2021;Gharbharan et al, 2020;Horby et al, 2021;Li et al, 2020a;Libster et al, 2021;Rasheed et al, 2020;Simonovich et al, 2020), while the other 15 were non-randomized studies with different designs (Abolghasemi et al, 2020;Alsharidah et al, 2021;Altuntas et al, 2021;Budhiraja et al, 2021;Donato et al, 2021;Duan et al, 2020;Hegerova et al, 2020;Joyner et al, 2021;Liu et al, 2020;Omrani et al, 2021;Salazar et al, 2020a;Shenoy et al, 2021;Xia et al, 2020;Yoon et al, 2021;Zeng et al, 2020), as detailed in Table S1. Two studies did not have a control group; nonetheless, one provided the relative mortality data upon multiple comparisons between patients receiving high vs. low titer plasma and between early (%3 days from hospitalization) and late treatment (Joyner et al, 2021), or comparing the effects of immediate plasma treatment toward plasma treatment only upon patient deterioration (deferred treatment) (Balcells et al, 2021), and they were thus both included. Similarly, Salazar et al provided multiple comparisons considering treatment time and plasma titer, all compared with a matched control group without treatment (Salazar et al, 2020a) and other three studies contained subgroup data for comparing early and late treatment, based on the severity of enrolled patients (Alsharidah et al, 2021;Donato et al, 2021;Horby et al, 2021).…”
Section: Resultsmentioning
confidence: 99%